Analisis Kesulitan Belajar Siswa Kelas III Dalam Menyelesaikan Soal Materi Operasi Hitung Perkalian pada Masa Pandemi Covid-19 - Asmahul Husnah; Muhammad Tahir; Lalu Hamdian Affandi (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2022)
Mathematics is seen as a difficult subject for students to understand, this is also supported by the number of students who do not like this learning. This study aims to determine the types of student difficulties in solving multiplication problems, the causal factors, and the teacher's efforts in overcoming students' difficulties in solving multiplication problems during the Covid-19 pandemic at SDN 40 Mataram. The type of research used is descriptive exploratory. The subjects used in this study were students of class III at SDN 40 Mataram totaling 14 people. Data collection techniques used are tests, interviews, and documentation studies. The results showed that 9 out of 14 students had learning difficulties in solving multiplication problems. Learning difficulties in solving multiplication problems that occur in class III include difficulties in understanding concepts, numeracy skills, understanding story problems, difficulties in writing numbers, using place values, suitability of steps/procedures. The causative factors are the use of memorization methods, limited face-to-face learning methods, lack of parental attention, lack of infrastructure, lack of student awareness, lack of teacher teaching variations. The teacher's efforts to overcome difficulties in solving multiplication problems include learning variations, increasing motivation and interest, using media, additional classes, collaboration between parents and teachers.